Health-related quality of life among children with epilepsy / Siti Khuzaimah Ahmad Sharoni, Juwairiyah Abdul Rahman, Mirrah 'Adilah Md Jamaludin, and Norfaiqah Mohd Radzi - Ahmad Sharoni, Siti Khuzaimah; Abdul Rahman, Juwairiyah (Faculty of Business Management, 2013)
This study examines the level of quality of life (QOL) among children with epilepsy and examines the association between epilepsy impact and memory or concentration among children with epilepsy. Besides, examines the association between health-related quality of life (HRQOL) and demographic data. Cross-sectional study was conducted at five Pediatric Ward and Pediatric Outpatient Clinic of selected hospitals for epilepsy children in area of Klang Valley and Kuala Lumpur. Malay version of the QOLIE-AD-48 had been used. The questionnaire was answered by108 respondents ages from 7 to 18 years old. The mean (SD) for overall QOL score was 63.03 (18.23). There was fair correlation between epilepsy impact and memory or concentration as the p-value < 0.05. For demographic data result, there was no correlation between health- related life quality with number of siblings (p-value > 0.05), races (p-value > 0.05), and parents education (p-value > 0.05), whereas HRQOL significantly associated with gender and age (p< 0.05). The overall scores of QOLIE-AD-48 show that children with epilepsy were in moderate level of QOL. The finding shows that impact of epilepsy affects the children memory or concentration. Most of the demographic data does not affect the HRQOL except gender and age.